IMPLEMENTASI METODE WEIGHTED PRODUCT DALAM SISTEM PENUNJANG KEPUTUSAN PEMBUANGAN MATERIAL NOT GOOD (NG) PRODUKSI - Mujahidin Mujahidin; Arif Budimansyah Purba; Tresa Agustian (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2019)
Bad Material is a product whose condition is Damaged or Not In accordance with a predetermined size, in the matter of this NG material can be determined what materials must be disposed of and what materials must be repaired. In the material there are several criteria that can be used as a yardstick to determine whether the NG material is directly discharged into production waste or not. To determine the NG material production can be done by using a weighted product support system. Ranking determination can be done by looking at the number of criteria in the alternative NG production by calculating weighted products can help in making decisions in the disposal of NG material and only choose one material to be disposed of into production waste whose status cannot be repaired again and the final result of the Weighted Product method has a final value that changes according to the number of alternatives.